Classic Biphasic Pulmonary Blastoma: A Case Report and Review of Literature - Awatif A. Jamal,; Wafaey M. Gomaa, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Pulmonary blastoma is relatively a rare aggressive tumour on adults with poor prognosis that usually presents at an early age than the nonsmall cell lung cancer. Pulmonary blastomas are subdivided in three subtypes: Well-differentiated foetal adenocarcinoma, classic biphasic pulmonary blastoma and pleuropulmonary blastoma. Classic biphasic pulmonary blastoma is composed of immature epithelial and/or mesenchymal tissues with similarity to an early embryonic lung. Pulmonary blastoma most commonly manifest as a solitary parenchymal mass on chest radiograph and Computerized Tomography. Symptoms are evident in 60% of cases due to the large tumour size. The World Health Organization differentiates pulmonary blastoma from pleuropulmonary blastoma and the well-differentiated foetal adenocarcinoma is included as a histological variant of adenocarcinoma. This report is the first case of classic biphasic pulmonary blastoma of a 16 years old female diagnosed at our department and treated by surgical intervention followed by chemotherapy. As for our knowledge, this is the first case reported in the Kingdom of Saudi Arabia. Extensive literature review of this category of lung malignancy is provided encompassing the clinical and pathological features, as well as the prognosis of this group of malignancy.